A new perspective on the photocatalytic action of titanium dioxide on phenol elucidated using comprehensive multiphase NMR. Issue 27 (1st July 2022) - Ghosh Biswas, Rajshree; Croxall, Mark P.; Lawrence, Reece T.; Soong, Ronald; Goh, M. Cynthia; Simpson, Andre J.
Abstract : First application of CMP-NMR to heterogeneous catalysis, we discover a region where organics experience restricted diffusion and are preferentially degraded. Abstract : Comprehensive Multiphase NMR (CMP-NMR) is a recently developed technique capable of simultaneously observing different phases – solutions, gels, and solids – while providing the chemical specificity of traditional NMR. With this new tool, the heterogeneous photocatalysis of phenol by titanium dioxide (P25 TiO2 ) is re-examined to gain information about the occurrence of reaction at different regions between the catalyst and the solution. It was found that the proportion of phenol in different phases changes over the course of the photodegradation period. The photocatalyst appears to preferentially degrade phenol molecules that are weakly associated with the surface, such that they have restricted mobility in a 'gel-like' state. Diffusion Ordered Spectroscopy (DOSY) corroborates the relative change in phenol signals between freely diffusing solution and diffusion restricted gels as measured using CMP-NMR. The surface of P25 TiO2 was found to foul over the course of the 200-hour photodegradation period that was monitored using the solid-state capabilities of the CMP-NMR. Finally, CMP-NMR showed differences in the photodegradation of phenol by P25 TiO2 to that of a TiO2 -nitrogen doped graphene quantum dot (NGQD) composite. With the latter composite, no fouling of the surface was seen over time. This application of CMP-NMR to the field of catalysis demonstrates its potential to better understand and study photocatalytic systems in general.